PROGNOSIS OF MYASTHENIA GRAVIS: A COMPREHENSIVE SYSTEMATIC REVIEW - Maharani, Shabrina; Ramadani, Latifah (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The complex disease progression and treatment challenges affect the overall prognosis in myasthenia gravis (MG) patients. Recent advancements in managing MG have brought about significant progress in attaining complete stable remission  as the treatment objective. This study aims to systematically review the prognosis of MG in literatures of the last 10 years.  Methods: This systematic review complied with the PRISMA 2020 standards and focused on full-text English literature published between 2014 and 2024. Articles such as editorials and review papers from the same journal, as well as submissions lacking a DOI, were excluded from consideration. Literature was sourced from online platforms like PubMed and SagePub.  Result: We found 627 articles on PubMed and 810 articles on SagePub. Restricting our search to the past decade (2014-2024), PubMed presented 425 articles, whereas SagePub presented 309 articles. From these, we selected 5 papers meeting our criteria, with 2 from PubMed and 3 from SagePub. Conclusion: Significant progress has been achieved in treating MG over the past decade. While some patients experience spontaneous remission, the majority require treatment with steroids or similar drugs. Other treatment modalities such as monoclonal antibody treatment, pulmonary function testing, and thymectomy can be employed to improve the prognosis of MG.